Mesquite pods to mezcal : 10,000 years of Oaxacan cuisines - Pérez Rodríguez, Verónica (Associate professor of anthropology); Morell-Hart, Shanti; King, Stacie M. (Austin : University of Texas Press, 2024)
"This volume explores the roots of traditional Oaxacan food, how it has evolved from its Mixtec origins, and how some traditions exist today; the essays included were written by archaeologists, ethnohistorians, anthropologists, and others with an interest in traditional Oaxacan food"--
The making of Oaxacan foodways / Andrea M. Cuéllar, Verónica Pérez Rodríguez, Shanti Morell-Hart, and Stacie M. King -- Food from the barranca : a 13,000-year perspective from the Yuzanú drainage of the Mixteca Alta / Aleksander Borejsza, Arthur Joyce, and Jon C. Lohse -- Archaic-period MRG-6 and the deep culinary roots of Oaxacan cuisine / Shanti Morell-Hart and Éloi Bérubé -- The cooked, the burned, and the modified : early formative cuisines and human-animal relations in the Mixteca Alta / Víctor E. Salazar Chávez and Jeffrey P. Blomster -- Perspectives on dietary variability in the Classic-period Valley of Oaxaca / Gary M. Feinman and Linda M. Nicholas -- Eating in the city : investigating the dietary impact of urban life in ancient Oaxaca / Verónica Pérez Rodríguez -- Nourishing the ancestors among the Zapotecs of the Valley of Oaxaca during the Late Classic and Postclassic periods / Robert Markens and Cira Martínez López -- Foodways and diet in the prehispanic Mixteca Alta : ceramic and isotope analyses of the Tomb 1 burial in Nduatiucu (San Felipe Ixtapa, Teposcolula) / Jennifer Saumur and Aurélie Manin -- Foregrounding food : Mixtec cuisine, identity, and ritual at Tututepec, Oaxaca / Marc N. Levine and Kathryn Puseman -- Preserving Oaxacan foodways in the face of conquest : a seed bank in the Nejapan Sierra Sur / Stacie M. King and Shanti Morell-Hart -- Oaxacan cuisine at Achiutla during the early colonial period : a story of resilience / Éloi Bérubé and Jamie E. Forde -- Itacate para el camino : prepared meals for prehispanic and colonial travelers / Nelly M. Robles García -- Isthmus Zapotec food : community, ecology, markets, makers / Anya Peterson Royce -- Maize cuisine on the move in the twenty-first century : persistence and migration of tejate, a traditional Mesoamerican maize and cacao beverage / Daniela Soleri, María del Carmen Castillo Cisernos, Flavio Aragón Cuevas, and David A. Cleveland.
Includes bibliographical references and index.
Online resource; title from digital title page (viewed on November 13, 2023).
JSTOR
Keywords: Cooking -- Mexico -- Oaxaca (State) -- History; Mixtec Indians -- Food -- Mexico -- Oaxaca (State) -- History; Zapotec Indians -- Food -- Mexico -- Oaxaca (State) -- History; Food habits -- Mexico -- Oaxaca (State) -- History; Mixtec cooking -- History; Zapotec cooking -- History; Diet -- Mexico -- Oaxaca (State) -- History; Mixtèques -- Alimentation -- Mexique -- Oaxaca (État) -- Histoire; Zapotèques -- Alimentation -- Mexique -- Oaxaca (État) -- Histoire; Habitudes alimentaires -- Mexique -- Oaxaca (État) -- Histoire; Cuisine mixtèque -- Histoire; Alimentation -- Mexique -- Oaxaca (État) -- Histoire; SOCIAL SCIENCE / General; Cooking; Diet; Food habits; Mixtec cooking; Zapotec cooking; Mexico -- Oaxaca (State); History; Essays; Electronic books